Effects of simulated space environmental conditions on cleanroom microbes - Cassilly, Chelsi D.; Chander, Atul M.; Vaughn, Jason A.; Kunstman, Kevin J.; Green, Stefan J.; Venkateswaran, Kasthuri; Bertone, Peter F.; Bahr, Curtis W.; Marcella, Samantha A.; Morris, Heather C. (Frontiers in Microbiology, 2025)
IntroductionMicroorganisms can have major impacts on the success of NASA’s missions, including the integrity of materials, the protection of extraterrestrial environments, the reliability of scientific results, and maintenance of crew health. Robust cleaning and sterilization protocols for spacecraft and associated environments are currently in place in NASA facilities, but microbial contamination should be further controlled and its impact on NASA’s missions and science must be minimized. To address this, air and surfaces across cleanrooms and uncontrolled spaces at the Marshall Space Flight Center were sampled and microbial burden and diversity were analyzed.MethodsA library of 82 microbial strains was isolated, curated, characterized, and a subset (n = 24) was subjected to simulated space environmental stressors, including desiccation, vacuum, proton radiation, and ultraviolet radiation. Out of these, four non-spore-former species (Arthrobacter koreensis PPS68, Paenarthrobacter sp. PPS72, Mycetocola sp. PPS117, and Erwinia sp. PPS120) exhibiting the highest resistance to tested stressors were selected for whole genome sequencing and comparative genomic, pan-resistomics and functional analyses.ResultsThe analysis revealed genomic features among these four species, encompassing genes critical for amino acid biosynthesis, carbohydrate metabolism, and stress response mechanisms. Erwinia sp. PPS120 had genomic features indicative of metabolic flexibility and stress response capabilities, particularly under oxidative stress conditions. Notably, strain A. koreensis PPS68 had unique genomic features predictive of resilience to desiccation and ionizing radiation, supported by genes for oxidative stress resistance, membrane stability, and nutrient acquisition. A. koreensis contains several genes which are also reported in established radioresistant strains, for predicted functions related to DNA-repair, osmoprotection, and efflux.DiscussionNASA cleanrooms harbor hardy non-spore-forming bacteria capable of surviving vacuum, ionizing radiation, and UV. Their adaptations to space stressors suggest limitations of today’s spore-centric bioburden assays to explore expanded planetary-protection standards. The modular exposure assay and reference genomes are important resources for microbial risk assessment, decontamination design, and safeguarding both robotic missions and closed human habitats in space and earth where microbial presence and colonization could compromise life-support systems and crew health.